Biocontrol effects of chemical molecules derived from Beauveria bassiana against larvae of Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) - Vivekanandhan, Perumal; Swathy, Kannan; Alahmadi, Tahani Awad; Ansari, Mohammad Javed (Frontiers in Microbiology, 2024)
In this study, we conducted tests on the isolation, identification, characterization, and extraction of chemical molecules from Beauveria bassiana against Tuta absoluta larvae. The enzyme responses of T. absoluta to the crude extract were examined 24 hours after treatment, and the number of dead larvae was calculated 24 and 48 hours after treatment. Molecular docking studies were conducted to assess the interaction of important molecules with the acetylcholinesterase enzyme. The larvicidal activity of crude chemicals from fungi was high 24 hours after treatment, with LC50 and LC90 values of 25.937 and 33.559 µg/mL, respectively. For a period of 48 hours, the LC50 and LC90 values were 52.254 and 60.450 µg/mL, respectively. The levels of acetylcholinesterase, α-carboxylesterase, and β-carboxylesterase enzymes were lower in the treatment group after 24 hours compared to the control group. The GC-MS test revealed that the crude extract consisted mainly of 9,10-octadecadienoic acid, which was the primary compound. Docking results indicated that 9,10-octadecadienoic acid showed a strong interaction with acetylcholinesterase (AChE). Our findings suggest that the chemical molecule 9,10-octadecadienoic acid derived from the entomopathogenic fungus B. bassiana is more toxic to T. absoluta larvae. We plan to conduct studies to test its effectiveness in semi-field conditions and to evaluate its stability in field conditions. We believe that this 9,10-octadecadienoic acid molecule could be used to control T. absoluta larvae in the near future without causing environmental pollution.